Use of neostigmine in capecitabine-induced paralytic ileus. Issue 5 (September 2013) - Mak, Gabriel; Ward, Robyn; Shehabi, Yahya; Venkateswaran, Ramya; Chin, Melvin
Paralytic ileus is a recognised side effect of the oral agent capecitabine. We present this report on a patient with metastatic colorectal cancer who was treated with capecitabine and presented with persistent paralytic ileus which did not respond to standard conservative measures. Neostigmine was administered safely, resulting in resolution of the paralytic ileus. This approach merits further investigation.